AN ADAPTER FOR AN ELECTRONIC DOOR LOCK - KHOO, Liqiang; NG, Matthew Mantik; LUO, Zhi Peng; PANG, Chee Kin Julius; MAH, Yung Ling (2025)
According to a first aspect of the present disclosure, there is provided an adapter for use in an electronic lock designed to be operatively coupled with a locking element of a door lock cylinder comprising a cylindrical housing having an open end and a receiver gear circumferentially surrounding an exterior of the cylindrical housing configured for operative engagement with a gear mechanism of the electronic lock, a frame coupled to the interior of the cylindrical housing, the frame including a plurality of openings, a plurality of retractable pins bundled in parallel with one another, the plurality of retractable pins adapted for coupling with the plurality of openings whereby some of the plurality of retractable pins conform to the locking element when the adapter is operatively coupled to the locking element.